INTEGRASI BUDAYA MALU DAN BERSALAH DALAM PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR - Anisah Raniyah Mumtazah; Bagus Dwi Prayoga; Dahlia Raviyanti; Farhan Dwi Saputra; Shandya Yasmin Anafari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses the culture of shame and guilt and their importance in shaping character and morals, especially for elementary school students. The culture of shame is a social system where individuals are expected to be self-aware, responsible, and follow ethics and morals. In shame cultures, an individual's response to criticism from others can significantly impact their behavior. The research emphasizes the importance of both shame culture and guilt culture in developing individuals' character and morals. Shame culture refers to a system where shame is a key factor in shaping behavior, while guilt culture focuses on individuals' feelings of guilt when they violate moral and ethical rules they believe in.Keywords: Culture Of Shame, Guilt Culture, Character Education.